Striatal Cholinergic Interneurons: How to Elucidate Their Function in Health and Disease - Mallet, Nicolas; Leblois, Arthur; Maurice, Nicolas; Beurrier, Corinne (Frontiers in Pharmacology, 2019)
Striatal cholinergic interneurons (CINs) are the main source of acetylcholine in the striatum and are believed to play an important role in basal ganglia physiology and pathophysiology. The role of CINs in striatal function comes mostly from extracellular recordings of tonically active striatal neurons in monkeys that are thought to correspond to CINs. Because these neurons transiently respond to motivationally relevant events with brief pauses flanked by bursts of increased activity, they are classically viewed as key players in reward-related learning. However, CIN modulatory function onto the striatal network has been mainly inferred from the action of acetylcholine agonists/antagonists or through CIN activation that are far from recapitulating the behaviorally relevant features of CIN activity in response to stimuli. New technical tools such as optogenetics now allow to specifically manipulate this sparse neuronal population and enable to reproduce features of CIN activity in response to behaviorally relevant stimuli. It is for instance now possible to investigate how short inhibition of CIN activity shapes striatal properties. Here, we review the related literature and show how these new techniques brought considerable insights into the functional role of CINs in normal and pathological states. These recent results raise a number of interesting questions and refining these approaches will require a better knowledge of CIN activity changes during behavior, particularly in rodents. Combined, as discussed, with computational approaches, optogenetics should thus contribute to further our understanding of the causal role of CINs in striatal circuits.